Oral tranexamic acid lightens refractory melasma. (13th May 2016) - Tan, Aaron Wei Min; Sen, Priya; Chua, Sze Hon; Goh, Boon Kee
Abstract: Background/Objectives: Melasma is a common acquired hyperpigmentary disorder, particularly among Asians and Hispanics, but its exact pathomechanism is poorly understood. Tranexamic acid has been found to lighten melasma by interfering with the interaction of melanocytes and keratinocytes by inhibiting the plasminogen/plasmin system. The aim was to evaluate the therapeutic effects of oral tranexamic acid in the treatment of melasma refractory to topical skin‐lightening agents. Methods: This retrospective study analyses patients with melasma recruited from a tertiary dermatological centre in Singapore between 1 August 2009 and 31 March 2011. The patients chosen had refractory melasma treated with oral tranexamic acid 250 mg twice daily in addition to pre‐existing combination topical therapy. Objective assessment using the physician's global assessment and melasma area and severity index (MASI) scores were performed based on a post‐hoc analysis of photographic records by three independent physicians. A paired t ‐test was used to evaluate the changes in the MASI scores pre‐therapy and post‐treatment. Statistical significance was defined as P < 0.05. Results: Altogether 25 patients were treated with tranexamic acid for a mean period of 3.7 ± 0.33 months, in addition to combination topical therapy. Their mean age was 47.2 ± 1.61 years. The mean MASI scores after tranexamic acid treatment (2.7 ± 1.6) were significantly lower ( P <  0.01) than those prior to treatment (8.8 ± 4.2). The mean improvement in scores was 69%. The follow‐up period was up to 6 months. Conclusion: Low‐dose oral tranexamic acid can serve as a safe and useful adjunct in the treatment of refractory melasma.